The Global Antimicrobial Resistance Epidemic Innovative Approaches and Cutting-Edge Solutions - Tellez-Isaias, Guillermo (IntechOpen, 2022)
Antibiotic resistance is a global health crisis. Misuse of antibiotics in humans, animals, food, and agriculture has compounded the situation. Bacterial infections have returned decades after medicines were first used. This book discusses antibiotic resistance and some of the organisms that pose immediate, serious, and alarming dangers. It highlights the need for a broader, more comprehensive approach to fighting bacterial infections, which may involve non-compound techniques (other than standard antibacterial drugs) that target bacteria or the host, such as antibodies, probiotics, phytobiotics, and vaccinations.